GENODIAGNOSTICS OF FMF IN ARMENIAN (Proceedings of the YSU B: Chemical and Biological Sciences, 2002)
Familial Mediterranean Fever (FMF) is a recessive inherited and ethnically restricted disease affecting populations of Mediterranean ancestry. In 1500 Armenian FMF patients we have found that mutations in the gene MEFV on chromosome 16 encoding pyrin/marenostrin, uniquely expressed in granulocytes, cosegregate with the FMF phenotype in affected pedigrees. The M694V homozygous genotype was found to be associated with a higher prevalence of renal amyloidosis and arthritis, compared with other genotypes. Our results should allow more-accurate identification of carriers and indicate an important role of genetic testing in the diagnosis of FMF.